Strangers next door? Indonesia and Australia in the Asian century - Lindsey, Timothy 1962-; McRae, Dave 1977- (Hart Publishing, 2018)
"There are no two neighbouring countries any where in the world that are more different than Indonesia and Australia. They differ hugely in religion, language, culture, history, geography, race, economics, worldview and population (Indonesia, 270 million, Australia less than 10 per cent of that). In fact, Indonesia and Australia have almost nothing in common other than the accident of geographic proximity. This makes their relationship turbulent, volatile and often unpredictable. Strangers Next Door? brings together insiders and leading observers to critically assess the state of Australia-Indonesia relations and their future prospects, offering insights into why the relationship is so important for Australia, why it is so often in crisis, and what this means for the future. This book will be of interest to anyone concerned with the Indo-Pacific region, Southeast Asia, Australia and Indonesia, and each country's politics, economy and foreign policy. It contains chapters that will interest specialists but are written in a style accessible to a general audience. The book spans a diverse range of subjects, including political relations and diplomacy, security and defence, the economy and trade, Islam, education, development, the arts, legal cooperation, the media, women, and community ties. Contributors assess the current state of relations in their sphere of expertise, and outline the factors and policies that could shape bilateral ties - and Indonesia's future - over the coming decades. University of Melbourne scholars Tim Lindsey and Dave McRae, both prominent observers and commentators on Indonesia and its relations with Australia, edited the volume,providing a synthesising overview as well as their own thematic chapters."...Provided by publisher